FROM READING TO CREATING: INTEGRATING RADEC FOR DEEPER LEARNING IN PRIMARY SCHOOLS - Nur Agus Salim; Muhammad Zainuddin; Jimmy Malintang; Rinovian Rais; Susintowati Susintowati (Universitas Islam Negeri Mataram, 2026)
Deep learning has become an important orientation in primary education because it emphasizes conceptual understanding, critical thinking, collaboration, communication, and the ability to transfer knowledge. However, primary school learning practices still tend to be procedural and do not fully support deep learning. The RADEC learning model (Read–Answer–Discuss–Explain–Create) has the potential to address this challenge through systematic learning stages centered on students’ active engagement. This study aims to analyze the implementation of the RADEC model to support deep learning in primary education through a Systematic Literature Review (SLR). This review was conducted in accordance with PRISMA principles by examining scientific articles published during the 2019–2025 period and sourced from Google Scholar, DOAJ, and Garuda. A total of 25 articles that met the inclusion criteria were thematically analyzed to map the implementation patterns of each RADEC stage and their relationship with the dimensions of deep learning. The synthesis results indicate that the Read and Answer stages contribute to conceptual understanding and critical thinking; the Discuss and Explain stages support collaboration and academic communication; and the Create stage encourages knowledge transfer and creativity. Nevertheless, the Create stage still needs strengthening in task design and product-based assessment. These findings affirm that RADEC is a relevant learning model for operationalizing deep learning in primary education.